Strategi Akselerasi Penerapan Smart City Di Kabupaten Wonosobo - Retnowati, Fanny; Eldo, Dwian Hartomi Akta Padma (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2024)
Smart City is a new strategy in urban development and management, evolving with technological advances. The concept aims to facilitate community activities and access to information. This research focuses on strategies for accelerating smart city implementation in Wonosobo Regency. The large population causes Wonosobo Regency to be included in an area with a high level of poverty in Central Java Province.This research is a type of qualitative research with descriptive methods. The data collection techniques used in this research were observation, interviews and documentation using snowball sampling techniques. The data validity technique used is triangulation. In implementing policies using Paul Collier's theory. The research location is the Wonosobo Regency Communication and Information Service. This research aims to identify strategies and efforts to accelerate smart cities as well as factors that influence the implementation of smart cities in Wonosobo Regency. The research results show that the acceleration of smart city implementation in Wonosobo Regency is progressing quite slowly, but the Regency Government continues to innovate in the form of quick wins in every dimension of smart city which is a strategy to accelerate the implementation of existing programs. has been formulated in the smart city master plan. The inhibiting factors found by researchers were budget, communication, resources, collaboration, quick wins, and mobility. Factors that support the acceleration of smart cities are regulations, bureaucracy, quick wins, achievements and technological developments.